Non-exhaust particle emissions under various driving conditions: Implications for sustainable mobility. (April 2020) - Beji, A.; Deboudt, K.; Khardi, S.; Muresan, B.; Flament, P.; Fourmentin, M.; Lumière, L.
Graphical abstract: Highlights: The mass of non-exhaust particles (NEP) is distributed between the accumulation and coarse modes. The number concentration of NEP is shared between the nucleation and accumulation modes. Brake wear particle emissions are highly dependent on brake pad temperature. Tire-road contact emissions are determined by vehicle speed, acceleration and deceleration. The chemical composition and shapes of non-exhaust particles differ according to the size modes. Abstract: Non-exhaust particle (NEP) emissions from road traffic contribute significantly to Particulate Matter (PM) pollution in urban areas. The primary objective herein is to develop the knowledge required to move toward more sustainable mobility. NEP emissions are studied by means of complementary experiments on chassis dynamometers, on test tracks and at the roadside. Laboratory tests demonstrate that brake wear particles (BWP) emissions can change with braking force and frequency. A brake pad temperature threshold exists, above which the rate of ultrafine particle emissions is quite high. Below this threshold, the BWP emissions are dominant in the accumulation and coarse modes. Test track measurements have demonstrated that tire-road contact particle (TRCP) emissions considerably modify the atmospheric PM background especially for the supermicron fraction. Their number size distribution highlighted an ultrafine and accumulation modes centered at about 40 nm and 200 nm, respectively. The TRCP level increases with vehicle speed and during the acceleration and deceleration phases. Roadside measurements in the urban environment confirm the presence of NEP in significant proportions, in both the accumulation and coarse modes. The chemical composition of NEP differs depending on the size mode: BWP mainly stem from the degradation of brake pad lining materials, while TRCP are a mixture of tire tread wear and re-suspended dust. The presence of Fe-rich particles nevertheless serves as a good indicator of the NEP contribution to PM at the roadside. Lastly, in considering the parameters influencing NEP emissions, a series of recommendations are offered in order to achieve a more sustainable mobility.